Competitiveness of Food Crop Commodity in Developing Countries: A Semi-Systematic Literature Review - Setiawan, Avi Budi; Mulyaningsih, Tri (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2022)
Agricultural commodities remain the primary source of exports for both developing and developed countries. However, inequity in competitiveness has emerged as a key concern as a result of discrepancies in economies of scale, efficiency, and government protection. The purpose of this study is to assess the competitiveness of main agricultural commodities in a number of developing countries. A semi-systematic review of the literature was employed as an analytical technique. The study's data was gathered from earlier research. The findings suggest that food crop commodities in poor nations have a low level of competitiveness. This is owing to the fact that the agricultural labor force in developing countries is largely comprised of unskilled employees, particularly women who are underpaid. In developing countries, four factors may have an impact on the competitiveness of food crop agricultural commodities. Availability of particular plant resources, technology, external and domestic demand, and domestic commodity and export pricing are just a few of them.